Formirovanie obraza optimal'nogo boevogo sostojanija metodami refleksii v processe psichologicheskoj podgotovki chokkeistov - Sopov, V. F. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
The organization of the psychological training in professional hockey club is based on the united application of the methods of reflection and purpose creating at the active participation of players and coaches. Besides the formation of the type of an optimum fighting condition there takes place the process of the formation of the motivation to professional game activity. The technology of the step-by-step comprehension of purposes and contents of methods and the means of their achievement by means of the reflective self-control proves to be effective. The application of the given technology creates the firm purpose of the professional attitude to the psychological training at hockey players.